Подход к построению предметной онтологии для экспертной системы «Сверхтвердые материалы» - Лебедева, А.А.; Фидаров, Т.З.; Скворцов, И.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The article outlines a new approach to the subject ontology design used to develop the expert system «Superhard materials». The ontology is being built as a program hierarchic structure of basic concepts and knowledge used by developers of this subject area and selected through the computer-expert systematization process.